2015
DOI: 10.3934/publichealth.2015.1.44
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Educational Intervention Improves Medication Safety Knowledge in Grandparents of Young Children

Abstract: Background and ObjectivesIncreasing grandparent-grandchild interactions have not been targeted as a potential contributing factor to the recent surge in pediatric poisonings. We hypothesized that in grandparents with a young grandchild, a single educational intervention based on the PROTECT “Up & Away” campaign will improve safe medication knowledge and storage at follow-up from baseline.MethodsThis prospective cohort study validated the educational intervention and survey via cognitive debriefing followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…8, 22, 31–34 Initiated in 2008, PROTECT is a public-private partnership led by the Centers for Disease Control and Prevention that aims to prevent unsupervised medication exposures by encouraging development and implementation of innovative exposure-limiting packaging (e.g., flow restrictors) and by updating and disseminating evidence-based educational messages on safe use and storage of medications that resonate with new generations of caregivers. To maintain or even accelerate reductions in preventable harm from pediatric medication exposures will require continuing efforts to address the medications that lead to frequent and disproportionate harm, including interventions that balance efficacy and feasibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8, 22, 31–34 Initiated in 2008, PROTECT is a public-private partnership led by the Centers for Disease Control and Prevention that aims to prevent unsupervised medication exposures by encouraging development and implementation of innovative exposure-limiting packaging (e.g., flow restrictors) and by updating and disseminating evidence-based educational messages on safe use and storage of medications that resonate with new generations of caregivers. To maintain or even accelerate reductions in preventable harm from pediatric medication exposures will require continuing efforts to address the medications that lead to frequent and disproportionate harm, including interventions that balance efficacy and feasibility.…”
Section: Resultsmentioning
confidence: 99%
“…Despite great success in reducing the numbers of pediatric poisoning deaths, 2 each year approximately a half million calls are made to poison centers after a young child accesses medication without adult supervision, 35 and from 2001–2008 the number of pediatric exposure calls that resulted in emergency department (ED) evaluation increased 24–32% depending on medication type. 6 Since then, renewed efforts to improve child safety packaging and education were initiated, 7, 8 and reducing ED visits for unintentional medication overdoses among young children was adopted as a Healthy People 2020 goal for the nation. 9 …”
mentioning
confidence: 99%
“…Being educated enables patients to understand and practice the written and oral guidelines and instructions of medication use, storage and handling better than those who are illiterate. Similarly, educational interventions have been shown to improve patients’ knowledge of their medication, including appropriate storage [ 27 , 28 ]. Likewise, pilgrims with underlying health conditions are more likely to be taking medications regularly and for longer periods of time compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…Only 28.2% of pilgrims accessed information on medication storage from the medication label in the current study. Studies have shown that not all medication users consult the medication label or the package insert for information [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In one study among Hajj pilgrims, only 54.2% reported that they do read the information on medications’ labels before using them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation